Leveraging Next-Generation Sequencing Application from Identity to Purity Profiling of Nucleic Acid-Based Products - Rucha Wadapurkar; Swarda Deo; Renuka Khanzode; Ajay Singh (Pharmaceutics)
Background/Objectives: The nucleic acid-based product (NAP) portfolio is expanding continuously and provides safer curative options for many disease indications. Nucleic acid-based products offer several advantages compared to proteins and virus-based products. They represent an emerging field; thus, their quality control and regulatory landscape is evolving to ensure adequate quality and safety. Next-Generation Sequencing (NGS) is mostly recommended for NAP identity testing, and we are leveraging its application for impurity profiling. Methods: We proposed a workflow for the purity assessment of NAPs through short-read Illumina NGS followed by data analysis of mRNA vaccine and pDNA samples. We determined the sequence identity, DNA and RNA contamination, off-target RNA contamination, and poly-A count with the proposed workflow. Results: Our workflow predicted most of the critical quality controls of mRNA vaccine and plasmid DNA samples, especially focusing on the identity and the nucleotide-based impurities. Additionally, NGS data interpretation also assisted in strategic decisions for NAP manufacturing process optimizations. Conclusions: We recommend the adaptation of incremental NGS data by regulatory agencies to identify nucleotide-based impurities in NAPs. Perhaps NGS adaptation under cGMP compliance needs to be deliberated with the regulatory bodies, especially focusing on the methods qualification and validation part, starting from the sample collection, NGS library preparation, NGS run, and its data analysis pipeline.